Defiant : growing up in the Jim Crow South - Hudson, Wade (Crown Books for Young Readers, 2021)
Memoir of civil rights activist Wade Hudson, covering his birth in 1946 in Mansfield, Louisiana through his coming of age in the middle of the Civil Rights Movement. Discusses how Hudson found his voice and began to use his writing to fight for his African American family and community.